Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species - Wang, Cheng-Bin; Perreau, Michel; Růžička, Jan; Song, Xiao-Bin (Zootaxa, 2017)
Sinobathyscia tianma sp. nov. (Coleoptera: Leiodidae: Cholevinae: Leptodirini) is described from Shanghai, China. The genus Sinobathyscia is redescribed with respect to the discovery of the male. Relevant morphological characters of the species examined are illustrated with colour plates, and their known distributions are mapped.